2008
DOI: 10.1180/minmag.2008.072.1.393
|View full text |Cite
|
Sign up to set email alerts
|

Influence of biofilms on transport of fluids in subsurface granitic environments — some mineralogical and petrographical observations of materials from column experiments

Abstract: Landfill and radioactive waste disposal risk assessments focus on contaminant transport and are principally concerned with understanding the movement of gas, water and solutes through engineered barriers and natural groundwater systems. However, microbiological activity can impact on transport processes changing the chemical and physical characteristics of the subsurface environment. Such effects are generally caused by biofilms attached to rock surfaces. This paper will present some mineralogical and petrogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 7 publications
3
12
0
Order By: Relevance
“…Finally, these filaments from the biotic experiment were observed to have locally etched the mineral substrate, and again this was not seen in the starting material. Similar biofilaments have been observed in other flow-through column experiments examining biofilm impacts on fluid transport through crushed diorite but under unpressurized conditions (Hama et al, 2001;Tuck et al, 2006;Coombs et al, 2008). Therefore, it can be concluded that although the starting material had been affected by the activity of microbial contamination, this was completely different from the microbial effects seen in the biotic column experiment.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Finally, these filaments from the biotic experiment were observed to have locally etched the mineral substrate, and again this was not seen in the starting material. Similar biofilaments have been observed in other flow-through column experiments examining biofilm impacts on fluid transport through crushed diorite but under unpressurized conditions (Hama et al, 2001;Tuck et al, 2006;Coombs et al, 2008). Therefore, it can be concluded that although the starting material had been affected by the activity of microbial contamination, this was completely different from the microbial effects seen in the biotic column experiment.…”
Section: Discussionsupporting
confidence: 76%
“…Finally, these filaments from the biotic experiment were observed to have locally etched the mineral substrate, and again this was not seen in the starting material. Similar biofilaments have been observed in other flow-through column experiments examining biofilm impacts on fluid transport through crushed diorite but under unpressurised conditions (Hama et al, 2001;Tuck et al, 2006;Coombs et al, 2008).…”
Section: Abiotic Column Experiments -Post-experimental Materialssupporting
confidence: 67%
See 2 more Smart Citations
“…It is known that ancient wood layers could produce enough organic acids during their buried process, which can accelerate the weathering process of the nearby granite bedrock with the chemical or biological reaction (Hama et al, 2001;Coombs et al, 2008). Based on the investigation in the field, a thick peat layer was buried under the ancient wood layer and its measured pH value is about 3.0.…”
Section: Iron Origin For Formation Of Iron Oresmentioning
confidence: 99%